2013
DOI: 10.1021/sc300148b
|View full text |Cite
|
Sign up to set email alerts
|

Microexplosions in the Upgrading of Biomass-Derived Pyrolysis Oils and the Effects of Simple Fuel Processing

Abstract: The development of biofuels produced from biomass-derived pyrolysis oils (bio-oil) requires a deeper understanding of the bio-oil vaporization required for catalytic hydrodeoxygenation, reforming and combustion processes. Through the use of high-speed photography, bio-oil droplets on a 500 °C alumina disk in nitrogen gas were observed to undergo violent microexplosions capable of rapidly dispersing the fuel. High speed photography of the entire droplet lifetime was used to determine explosion times, frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…When it comes to using liquid fuels, they are easier to transport (high density) and storage under controlled conditions as compared to solid fuels [5]. Compared to other renewable liquid fuels, pyrolysis bio-oils are derived from biomass and other sources of waste (approximately 10% of the world's energy resources) [6] have been successfully established as feasible renewable fuel sources to promote the 2 of 22 substitution of fossil fuels [7][8][9]. Biomass utilisation to produce value-added products in all forms (liquid, gas and solid fuels) has been of great interest to researchers around the world.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to using liquid fuels, they are easier to transport (high density) and storage under controlled conditions as compared to solid fuels [5]. Compared to other renewable liquid fuels, pyrolysis bio-oils are derived from biomass and other sources of waste (approximately 10% of the world's energy resources) [6] have been successfully established as feasible renewable fuel sources to promote the 2 of 22 substitution of fossil fuels [7][8][9]. Biomass utilisation to produce value-added products in all forms (liquid, gas and solid fuels) has been of great interest to researchers around the world.…”
Section: Introductionmentioning
confidence: 99%
“…This liquid could act as an electrolyte, catalyzing solid-liquid reactions that produce char [31,32]. This kind of behavior has been specially proposed for pure cellulose [8,[33][34][35], however it could be extrapolated to other biomass constituents. Dufour et al [24,25] have shown that during thermal degradation each biomass component passes through a thermoplastic state, where visco-elastic properties depend strongly on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-emulsion droplet combustion is a relevant example of a technology where microexplosions are important. During combustion, aerosols may be released totally or partially, destroying the mother droplet [19,20]. Microexplosion of droplets suspended on a thermocouple is commonly studied using fast speed cameras (> 1000 fps) to visualize morphological changes as a function of temperature and time [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Shuhn et al [26] described the swelling, bubbling, aerosol ejection phenomena during micro-explosions of fast pyrolysis bio-oil blends with diesel. Teixeira et al [19] found that the presence of high molecular weight compounds (1000 Da) in the bio-oil is important for the formation of microbursts. Filtration of these compounds (probably pyrolytic lignin) reduces the frequency of micro-explosions by 50 %.…”
Section: Introductionmentioning
confidence: 99%